2018
DOI: 10.26644/em.2018.001
|View full text |Cite
|
Sign up to set email alerts
|

Cardiorespiratory Fitness and Leisure Time Physical Activity are Low in Young Men with Elevated Symptoms of Attention Deficit Hyperactivity Disorder

Abstract: Exercise Medicine 2018; 2:1 | https://doi

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 31 publications
0
4
0
Order By: Relevance
“…While not seen in our data, adults with ADHD tend to be less physically active than their neurotypical peers [ 106 , 107 ], and therefore, may especially benefit from an exercise intervention that increases fitness. Given that inhibitory control is the hallmark of executive dysfunction associated with ADHD [ 108 ] and may be especially sensitive to chronic exercise adaptations [ 109 ], exercise programs that increase CRF in adults with ADHD may be supportive of their inhibitory control functioning and should be explored in future research.…”
Section: Discussionmentioning
confidence: 79%
“…While not seen in our data, adults with ADHD tend to be less physically active than their neurotypical peers [ 106 , 107 ], and therefore, may especially benefit from an exercise intervention that increases fitness. Given that inhibitory control is the hallmark of executive dysfunction associated with ADHD [ 108 ] and may be especially sensitive to chronic exercise adaptations [ 109 ], exercise programs that increase CRF in adults with ADHD may be supportive of their inhibitory control functioning and should be explored in future research.…”
Section: Discussionmentioning
confidence: 79%
“…When compared to their neurotypical peers, the average estimated CRF for participants with ADHD was not statistically different. Prior research has reported lower CRF in men with ADHD ( K. Fritz & O’Connor, 2018 ; Jeoung, 2014 ), whereas our sample was predominantly women (ADHD = 64%; control = 75%), suggesting there may be gender or sex differences to explore. It is also important to note that the association between fitness and perceived stress was only observed for individuals with mild ADHD symptoms.…”
Section: Discussionmentioning
confidence: 69%
“…Higher CRF, which reflects our ability to intake and circulate oxygen throughout the body to meet task demands ( Caspersen et al, 1985 ), has been associated with better mental health and fewer incidents of mental illness in neurotypical populations ( Kandola, Ashdown-Franks, Hendrikse, et al, 2019 ; Schuch et al, 2016 ) and individuals with stress-related exhaustion disorder ( Lindegård et al, 2019 ). Importantly, there is some evidence to suggest that those with ADHD may have lower CRF ( K. Fritz & O’Connor, 2018 ; Jeoung, 2014 ) and higher incidences of mental illness ( C. M. Jensen & Steinhausen, 2015 ). However, the relationship between CRF and mental health in adults with ADHD has yet to be explored.…”
Section: Introductionmentioning
confidence: 99%
“…Despite these documented benefits, PA engagement by people with ADHD tends to be lower than their neurotypical peers (i.e., those with typical neurodevelopment; Cook et al, 2015;Fritz & O'Connor, 2018;Quesada et al, 2018) and, in turn, they experience elevated risk of metabolic conditions (e.g., metabolic syndrome and Type 2 diabetes; Landau & Pinhas-Hamiel, 2019). It is conceivable that specific symptoms of ADHD may create unique barriers to engaging in regular PA (Pontifex et al, 2014).…”
Section: Introductionmentioning
confidence: 99%